2016
DOI: 10.1038/ncomms13346
|View full text |Cite
|
Sign up to set email alerts
|

CD301b+ dendritic cells stimulate tissue-resident memory CD8+ T cells to protect against genital HSV-2

Abstract: Tissue-resident memory CD8+ T (CD8 TRM) cells are an essential component of protective immune responses at barrier tissues, including the female genital tract. However, the mechanisms that lead to the initiation of CD8 TRM-mediated protective immunity after viral infection are unclear. Here we report that CD8 TRM cells established by ‘prime and pull' method confer protection against genital HSV-2 infection, and that IFN-γ produced by CD8 TRM cells is required for this protection. Furthermore, we find that CD8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 48 publications
(85 reference statements)
2
71
1
Order By: Relevance
“…Recent murine studies demonstrate that memory CD103 + CD8 + T cells in the nasal mucosa prevent dissemination of pulmonary influenza virus infection to the lungs (Pizzolla et al., 2017). Animal studies have also demonstrated that TRMs mediate local protection against genital HSV‐2 infections (Shin, Kumamoto, Gopinath & Iwasaki, 2016). Therefore, induced immune cell protection against STIs in humans would likely require a potent resident memory T‐cell population (Iwasaki, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent murine studies demonstrate that memory CD103 + CD8 + T cells in the nasal mucosa prevent dissemination of pulmonary influenza virus infection to the lungs (Pizzolla et al., 2017). Animal studies have also demonstrated that TRMs mediate local protection against genital HSV‐2 infections (Shin, Kumamoto, Gopinath & Iwasaki, 2016). Therefore, induced immune cell protection against STIs in humans would likely require a potent resident memory T‐cell population (Iwasaki, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As women age and remain sexually active, protection of the FRT at all ages is essential. Our findings are particularly relevant to HIV prevention, because most CD8 + T cell studies focus on the evaluation of blood T‐cell responses, which do not correlate with the protective effects of resident T cells in the FRT (Shin et al., 2016; White et al., 2001). …”
Section: Discussionmentioning
confidence: 99%
“…102,103 CD301b + LP DCs are required to activate vaginal T RM s upon vaginal herpes virus re-challenge. 104 In contrast, dorsal root ganglia resident T RM s are re-activated by recruited monocyte-derived DCs 105 and skin CD8 + T RM s are reactivated by almost any directly infected epidermal cells carrying cognate antigens. 106 Recent results have demonstrated that FRT T RM cells undergo expansion and differentiation in situ during re-challenge.…”
Section: Tissue Specific Features Of Trm Cellsmentioning
confidence: 99%
“…Thus, in addition to a sentinel system, mucosal T RM function as a robust self-sufficient defense system and can function independent of circulating T cells. 104,107 …”
Section: Tissue Specific Features Of Trm Cellsmentioning
confidence: 99%
“…Tissue-resident memory T cells (T rm ) are compartmentalized away from the circulating pool via the expression of the tissue-retention signals CD69 and/or CD103 [58]. They can be directed against viruses that invade these sites: for example, HBV-specific CD8 + T rm have been found in the human liver [59], murine herpes simplex virus 1-specific T rm in the lamina propria of the vagina [60] and human influenza A-specific T cells in the lung [61]. CD8 + T rm provide rapid antigen-specific recall responses in situ and therefore act as highly functional defence specialists, with adaptations imposed by their local niche.…”
Section: Tissue Residencymentioning
confidence: 99%